2008
DOI: 10.1016/j.jpubeco.2007.10.002
|View full text |Cite
|
Sign up to set email alerts
|

The aging population and the size of the welfare state: Is there a puzzle?

Abstract: This paper tests several leading hypotheses on determinants of government expenditure. The purpose is to avoid omitted variables bias by testing the prominent theories in a comprehensive specification, to identify persistent puzzles for the current set of theories, and to explore those puzzles in greater depth by looking at the composition of government expenditure and the level of government at which it takes place as well as its magnitude. Using Global Financial Statistics data from the IMF covering over 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 6 publications
0
23
0
3
Order By: Relevance
“…Some of these studies rely on data from a single country, including the USA (MacManus 1995 (2002) argue that a higher old-age dependency ratio causes lower labor tax-rates and less generous social transfers. This result has been heavily criticized in several papers including Disney (2007), Simonovits (2007) and Shelton (2008). across all age-groups.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Some of these studies rely on data from a single country, including the USA (MacManus 1995 (2002) argue that a higher old-age dependency ratio causes lower labor tax-rates and less generous social transfers. This result has been heavily criticized in several papers including Disney (2007), Simonovits (2007) and Shelton (2008). across all age-groups.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…A similar variable, using 70 instead of 65 as threshold age, has recently been employed by Krieger and Ruhose (2013) to study the impact of population aging on family benefits and educational expenditures. Related empirical studies have operationalized population aging using old-age dependency ratios (Shelton, 2008;Tepe and Vanhuysse, 2009) or the share of elderly to total population (Harris et al, 2001;Poterba, 1997;Sanz and Velázquez, 2007). However, we think that these indicators are less appropriate for our purposes, because they capture relative voting power of elderly citizens only indirectly.…”
Section: Econometric Modelmentioning
confidence: 99%
“…In the last decades, empirical studies have demonstrated that population aging in fact influences government spending components including social welfare, health and education (Harris et al, 2001;Krieger and Ruhose, 2013;Poterba, 1997;Sanz and Velázquez, 2007;Shelton, 2008;Tepe and Vanhuysse, 2009). Furthermore, evidence based on survey data reveals age-specific preferences regarding welfare and educational spending (Boeri et al, 2001;Bonoli and Häusermann, 2009;Cattaneo and Wolter, 2009;Sørensen, 2013).…”
Section: Philipp Jäger Torsten Schmidt 1 Introductionmentioning
confidence: 99%
“…Easterly and Levine (1997) report a strong negative correlation between ethnic fragmentation and the provision of public goods in African countries. Shelton (2008) finds that central government expenditures on health care are lower in countries with greater ethnic fractionalization. We control for this effect by adding an ethnic fractionalization index developed by Desmet et al (2012).…”
Section: Additional Control Variablesmentioning
confidence: 99%